2021
DOI: 10.1038/s41598-021-97381-6
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the avoidability of drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome

Abstract: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a rising morbidity amongst hospitalized patients. Whilst clinical protocols for the management of individual DRESS cases have been well established, determination of potential prevention of these cases by utilizing novel “avoidability” tools has remained unexplored. This retrospective study reviewed records of patients who presented to the emergency department of Weill Cornell Medicine-affiliated Hamad General Hospital, Doha Qatar with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Our results demonstrated a nonsignificant difference between the two rating specialties (general physicians and clinical pharmacists) in the proportion of EA and ED. Physicians and pharmacists have shown comparable results in utilizing other diagnostic and causality determination tools, including the updated RUCAM scale amongst others [ 10 , 22 , 23 ]. This suggests that these tools are inherently objective, and do not require extensive knowledge of clinical pharmacology for their clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated a nonsignificant difference between the two rating specialties (general physicians and clinical pharmacists) in the proportion of EA and ED. Physicians and pharmacists have shown comparable results in utilizing other diagnostic and causality determination tools, including the updated RUCAM scale amongst others [ 10 , 22 , 23 ]. This suggests that these tools are inherently objective, and do not require extensive knowledge of clinical pharmacology for their clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of avoidability is a fast-evolving topic in pharmacoepidemiology [2][3][4][5]. We were the first to explore the potential utility of the well-validated Liverpool adverse reaction avoidability tool (LAAT) in patients with DRESS syndrome [6]. In our published report exploring the clinical utility of the LAAT in patients with DRESS syndrome (N = 16) and median (IQR) RegiSCAR and J-SCAR scores of 6 (5-6.8) and 5 (4-5.8), respectively, we found that about 60% of the DRESS syndrome drug pairs were rated as "avoidable" ("probable" or "definite").…”
Section: To the Editormentioning
confidence: 99%